Impact of lifestyle medicine program “viva mejor” in knowledge, attitudes and practices in diet and physical activity in adventist organization officials - Cari-Huanca, Gloria (2018)
Introduction: The objective of the present study was to evaluate the effectiveness of the "Viva Mejor" program in improving knowledge, attitudes and practices on healthy eating and physical exercise. Methods: Experimental study of intervention with a duration of three months, in which participated 38 officials of the Adventist Organization in Peru (Union Peruana del Sur), held in the district of Miraflores Lima Peru. The program developed practical theoretical workshops for both healthy eating and physical exercise, motivated healthy eating through the model "healthy dish" that promotes the daily consumption of whole grains, vegetables, fruits, legumes and proteins of vegetable origin, they were also motivated to perform daily physical exercise under the supervision of an instructor. Results: The results on healthy eating showed that the knowledge of the participants increased by 18.4%, their attitudes increased by 10.5%, the practices of consumption of whole grains, vegetables, fruits, and proteins of vegetable origin increased by 39.4%. Regarding physical exercise their knowledge increased by 13.2%, their attitudes by 2.6% and their practice of three or more times physical exercise per week improved by 73.6%. The difference in medians before and after the intervention was statistically significant according to the wilcoxon test, value p = .000. Conclusion: The implementation of the "Viva Mejor" lifestyle medicine program showed significant favorable changes in the population studied in terms of knowledge, attitudes and practices of eating and physical activity. Key words: Diet; Physycal activity; Nutricional status; Lifestyle Medicine. (source: MeSH NLM)   DOI: 10.25176/RFMH.v18.n2.1286